Strategi Peningkatan Kapasitas Paralegal Desa Deme Dua Dalam Penanganan Kasus Hukum Dengan Prinsip Etika - Nurwita Ismail; Muslim Kasim; Nurlin Lasambo (CV. Multi Kreasi Media, 2025)
Along with the times, the number and complexity of legal cases in the village also increased. Paralegals who have a good capacity can help handle these cases more efficiently and effectively. In remote villages, access to professional lawyers or legal aid agencies is often limited. Paralegals who have a good capacity can be an important alternative in providing legal assistance. Paralegals who have adequate capacity can play an active role in resolving conflicts at the local level, such as land disputes or family matters, so there is no need to take them to higher courts. As mandated by Article 9 of Law Number 16 of 2011 concerning Legal Aid. It is undeniable that the handling of legal cases must be based on ethical principles to maintain public integrity and trust. Paralegals trained in ethical principles can ensure that the case handling process is carried out fairly and transparently. Villages have a very important role in supporting the implementation of legal aid in their communities, namely by providing Facilitation of Access to Training and Education, in addition to which Villages can collaborate with legal aid institutions, universities, and non-governmental organizations to hold training and workshops for paralegals and the community, and can initiate legal counseling programs involving paralegals to disseminate legal knowledge to residents. Village communities can be facilitated to gain access to legal and educational information related to their rights.